2021
DOI: 10.3920/jiff2020.0128
|View full text |Cite
|
Sign up to set email alerts
|

Stable isotope ratio analysis for the characterisation of edible insects

Abstract: Entomophagy, or the act of eating insects, has been practiced since ancient times, but it started to gain more popularity, especially in Western countries, only recently. As sustainability is one of the current emerging themes, the inclusion of insects in our diet is a valid alternative that might help reduce the amount of water and land used for livestock and the associated emissions of greenhouse gasses. Moreover, insects are a source of protein, fibres, vitamins, minerals and fats. Edible insects are consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 60 publications
0
19
0
Order By: Relevance
“…The average δ 13 C values recorded for BSF in this study ranged between -18.8‰ (defatted BSFP reared on ED1) and -14.9‰ (fat matter of the BSFL fed on ED4) (Tables 6-7). These results lay in the upper part of the range described by Pianezze et al (2021) (from -31.2 up to -12.2‰, on defatted matter) studying the isotopic ratios of 35 different edible insect species. For the diets' formulation, it was not possible to find corn gluten (C4 plant) in the retail market, in place of which was used wheat gluten (C3 plant).…”
Section: Isotope Analysismentioning
confidence: 62%
See 1 more Smart Citation
“…The average δ 13 C values recorded for BSF in this study ranged between -18.8‰ (defatted BSFP reared on ED1) and -14.9‰ (fat matter of the BSFL fed on ED4) (Tables 6-7). These results lay in the upper part of the range described by Pianezze et al (2021) (from -31.2 up to -12.2‰, on defatted matter) studying the isotopic ratios of 35 different edible insect species. For the diets' formulation, it was not possible to find corn gluten (C4 plant) in the retail market, in place of which was used wheat gluten (C3 plant).…”
Section: Isotope Analysismentioning
confidence: 62%
“…The biochemical bases of such isotope fractionation have been masterfully formulated by De Niro and Epstein (1978). However, in our case the situation was quite different from other studies found in literature (Pianezze et al, 2021), for this study describes variable carbon isotope fractionation between the animals' compartments with respect to the isotopic abundance of the diets. In this study, the main (if not the sole) source of lipids in the BSF diet was the corn oil, whose δ 13 C value was very stable at -16.3‰ and highly enriched with respect to C3 metabolism plant oils (e.g.…”
Section: Isotope Analysismentioning
confidence: 67%
“…The δ ( 13 C) of the fat and the protein fraction of meat are known to be correlated, as reported in the literature [ 30 , 31 , 32 ]. Nevertheless, to exclude the lack of additional information derived from the analysis of the δ ( 13 C) of the fat fraction, a subset of beef muscle samples was measured to assess this parameter.…”
Section: Resultsmentioning
confidence: 90%
“…Other explanations for the isotopic evidence, such as smaller consumption of meat in a dried/cured form (Speth, 2017) or mushroom consumption (O'Regan, Lamb and Wilkinson, 2016), may explain Neanderthal trophic‐level values better but are less masculine‐sounding. In addition, the isotopic signature in bone for the consumption of other protein sources like insects are currently unknown (Pianezze et al., 2021). Henry and colleagues (2014) argue that Neanderthals were sophisticated gatherers of plant foods for nutrition and medicine and that this suggests specialized gathering roles—but they are careful to say that these are not necessarily women's roles.…”
Section: Sex and Gender Issues In Paleoanthropologymentioning
confidence: 99%